(3GdMce GdYWGFjIs - (3GdpErSncrfnOQj, CHh GdaVd, GHf nYnWGA Gddg, JGL GdOjf, CMeO Hf eMeO Hf YHO GdcQje, (B709 (3gs ((3YeQ GdTQfHGdjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejfYdGeI GdGYJeGO Ydi GdYed fbUGf GdQLGA YfO hLhO GdRdd EQGOJc GdJLQjO eY EbGeI Gddg EjGc aj GdCSHGH ef GdTghI GdNajIs
(3BNQgG (B:s
(3jG ef JLdi HceGd HgGFg aJMbbJ YXeI GdCSQGQ cja jNai hCfJ GdXGgQ Ce cja JZjH hCfJ GdQbjH GdMGVQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 221s
(3eYLe GdeDdajf(B: 1 / 275s
(3cTa GdXfhf(B: 1 / 675s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs